Effect of Foliar application with Abscisic acid and gibberellic acid on morphological and physiological of Lettuce plant under salt stress conditions (Damascus University Journal of agriculture sciences, 2024)
This experiment was carried out in the Faculty of Agriculture ,Damascus University, during the period (2019 – 2020), to study the effct of Gibberellic acid and Abscisic acid on some morphological parameters of letus plant under salt stress conditions.Letus seeds() wer soaked in gibberellic acid (0,50,100ppm)for24h, then cultured in a mix of turp and perlite(1;1).NaCl was added(0,50,100,150ppm) after one week of culturing, ABA was foliar sprayed (0,5,10ppm) five times with 7 days intervals.Data showed that gradul increase in salt concentration resulted in gradul decrease in all studied parameters, On the other hand, treatment with gibberellic acid and abscisic acid increase plant hight, leaf number, leaf area, chlorophy(a,b) and carotene concentrations under salt stress conditions. The best values, however, were observed when GA3(50ppm) was added in combination with ABA(10ppm) comparing with all other treatments and with control which resulted in the lowest.
Keywords: Lettuce; Salt stress; Abscisic acid; Gebrilic acid